Asia-Pacific Regional Outlook. (Policy Papers; Policy Paper ;, 2005)
Looking ahead, prospects are relatively bright. Regional growth is expected to amount to 6 percent both this year and next, propelled by vigorous exports and strong domestic demand in China and India. Meanwhile, headline inflation is expected to remain around 3-3 1\2 percent, as lower food prices offset the impact of higher oil prices. At the same time, the region's current account balance is forecast to remain around 3 percent of GDP, albeit with large changes in its distribution.